Achievements and perspectives in designing a set of convergence indicators in European higher education - Alina Mihaela Dima; Simona Vasilache; Valentina Ghinea; Simona Agoston (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The paper is discussing the need for convergence in European higher education, as it was claimed and negotiated in the last decade, accompanied by the results and prospects of a research project advancing and testing a credible set of indicators of convergence in the European Higher Education Area. The main limitations and problems are addressed to, together with an overview of the indicators proposed, and of the ways of advancing the research in the field.
Keywords: 650; convergence indicators; higher education